A spontaneous bilateral tubal pregnancy: A case report. Issue 38 (September 2018) - Xu, Hong
Abstract: Rationale: Ectopic pregnancy (EP) is a condition in which a fertilized oocyte implants outside the uterine. Spontaneous bilateral tubal pregnancies are the rarest form of ectopic and are considered spontaneous when no fertility treatments are involved. There are few prior cases. Here I report a case of spontaneous bilateral tubal pregnancy. Patient concerns: A 24-year-old female with long lasting vaginal bleeding of 29 days duration. Diagnoses: Transvaginal ultrasound observed small complex masses on both adnexal sides without intrauterine gestational sac, and the hCG level was 21438 IU/L. But diagnosing based only on imaging findings and blood test result was difficult. Interventions: Operative laparoscopy with salpingectomy bilaterally. Outcomes: Villi were clearly shown in both resected tubes. A spontaneous bilateral tubal pregnancy was confirmed finally and the patient recovered uneventfully. Lessons: Women of reproductive age with irregular menstruation should get access to diagnosis and appropriate treatment without delay. Salpingotomy should also be considered if the patient had a strong wish for future pregnancy. Developments of diagnosis and management of such condition are strongly called for.